The role and significance of regulatory resolutions of the supreme court of the Republic of Kazakhstan in the current laws and regulations system - Turegeldiyev, Bakdaulet; Үessenaliyev , Аskat; Askarbekkyzy , Nazira (BULLETIN of L.N. Gumilyov Eurasian National University Law Series, 2024)
This article emphasizes the role and significance of Supreme Court rulings of Kazakhstan within the current system of laws and regulations of that nation. The authors explore their functional purpose and place in terms of sources of law while analyzing their relationship to legislation and other documents of law. Special focus is paid to aspects related to law-making activities by this body as well as any impact they might have on law enforcement practice and legislation development and potential ability of rulings of this court to clarify problematic areas related to understanding the law or enforcement thereof. The normative decisions of the Supreme Court serve to clarify norms of law and regulate their application in everyday society life, meeting all requirements established within legal framework. Judicial practice analysis yields useful results used as sources of law; each year more regulatory rulings of the Supreme Court become used in law enforcement practice to resolve major disputes more efficiently. This article reviews the key principles and criteria regulatory decisions must meet to successfully fill gaps in legislation and create an integrated law enforcement practice across Kazakhstan. The authors underscored the significance of regulatory rulings for eliminating ambiguities and disputes when it comes to interpretation of laws as well as creating an orderly legal environment that provides predictability